PERAN KEPOLISIAN DALAM UPAYA PENEGAKAN HUKUM TERHADAP PENIPUAN SECARA ONLINE - Nasrin Nasrin; Kifli (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The title of this research is The Role of the Police in Law Enforcement Efforts Against Online Fraud. This research aims to determine the role of the Police in law enforcement efforts against online fraud. This research is a normative legal research using a statutory approach, a conceptual approach, a historical approach, and a philosophical approach. The results of this research conclude that the police's efforts in enforcing criminal law against online fraud are first carried out through investigation, this investigation stage is the first stage carried out by investigators in investigating criminal acts and the most difficult stage in the investigation process, this is because investigators must be able to prove the crime that occurred and how and the causes of the crime in law enforcement. Factors inhibiting police law enforcement against online fraud include legal factors, infrastructure, law enforcement, operational costs and losses, and societal factors. Law enforcement officials, specifically the police, must be more innovative in addressing advances in technology and information. This is because, as technology and information advances, perpetrators are increasingly facilitated in committing crimes. This will facilitate their investigations and keep pace with the increasingly sophisticated rise in crime, particularly online fraud. The government, in particular, needs to strengthen existing laws and regulations to minimize and prevent crime.